(untitled) (The Review of Diabetic Studies, 2025)
This study aimed to identify the role of integration between nursing and social work and its impact on improving the quality of health care through a field study conducted in private hospitals in the city of Riyadh. This was achieved by measuring the level of communication and coordination between health care teams, the psychological and social support provided to patients, and the reflection of this integration on treatment quality and beneficiary satisfaction. The study adopted the descriptive analytical approach, and an electronic questionnaire designed via Google Drive was used. The questionnaire consisted of (32) statements distributed across four main dimensions and was applied to a convenience sample of (40) social workers and nurses working in hospitals in Riyadh. Data were analyzed using the SPSS program, where Cronbach’s alpha coefficient was calculated to assess reliability, along with means, standard deviations, and simple regression analysis. The results showed a very high level of reliability for the instrument, with an overall coefficient of (0.963). The findings also revealed a high overall level of agreement across all study dimensions. The dimension of psychological and social support for patients ranked first with a mean of (3.96), followed by the dimensions of communication and coordination between health care teams and professional knowledge and skills with a mean of (3.84), while the dimension of health care quality ranked last with a mean of (3.80). The results of the regression analysis further confirmed the existence of a statistically significant effect of integration between nursing and social work on improving the quality of health care, with the explanatory power of the model reaching (76.9%). The study concluded that enhancing professional integration between nursing and social work represents a fundamental approach to improving the patient experience and ensuring the provision of comprehensive health care that takes into account physical, psychological, and social aspects.